Gambaran Pengetahuan Sikap Dan Perilaku Pengunjung Dalam Pengelolaan Sampah Di Pantai Mertasari Tahun 2020 - Ayu Intan Sari; Dewa Ayu Agustini Posmaningsih (Jurnal Kesehatan Lingkungan (JKL), 2021)
Garbage is one that affects beach tourism, the problem of cleanliness of garbage seems to be an important problem that must be addressed at the beach. The impact of waste on the environment on the beach can kill coral reefs, marine life, and humans. The condition of the beach tourism environment polluted by garbage will reduce the attractiveness of tourists to visit the beach because it seems dirty The purpose of this study was to determine the knowledge, attitudes and behavior of visitors in waste management at Mertasari beach in 2020. This study used a descriptive method with data collection techniques with questionnaire sheets. The results of the study of visitor's knowledge showed that 28 people (35%) had poor knowledge in waste management, 22 people (27.5%) had negative attitudes towards waste management and 28 (35%) had poor behavior. good in waste management. It is recommended that the manager of Mertasari Beach be expected to collaborate with community leaders to conduct training on waste management, make regulations regarding sanctions if littering.As well as puskesmas and BUMDES in supervision and monitoring, providing health counseling by providing information on waste management by using leaflets , while BUMDES facilitates all needs in an effort to increase knowledge on how to manage waste such as adequate landfills.